Bentuk dan Makna dalam Lelakaq Sasak pada Masyarakat Lombok Nusa Tenggara Barat (Sebuah Analisis Wacana) - Mudarman (Lembaga Bale Literasi, 2024)
This study aims to describe and explain the form and meaning of lelakaq Sasak in the Lombok community, West Nusa Tenggara. This study is a qualitative descriptive study in the form of content analysis. The data of this study are in the form of words, phrases, clauses and sentences related to the form and meaning of lelakaq Sasak in the Lombok community, West Nusa Tenggara. Data were collected using recording techniques, repeated readings heuristically and hermeneutically. The sampling technique used was purposive sampling. Data were analyzed using interactive techniques with steps including data reduction, data presentation, and drawing conclusions/verification. The results of this study indicate that (1) the form of lelakaq Sasak is lelakaq in the form of advice, and (2) the meaning of lelakaq Sasak in the Lombok community has a religious meaning. This lelakaq has a moral message and message material. However, the most is a moral message.